Globalization and Capitalist Geopolitics Sovereignty and state power in a multipolar world - Woodley, Daniel (Taylor & Francis, 2015)
In a period of increasing geopolitical insecurity and economic instability this title provides an authoritative yet accessible commentary on debates on capitalism and globalization in the wake of the financial crisis.